Peran Kepemimpinan terhadap Perubahan Organisasi Di Himpunan Mahasiswa Prodi Manajemen - Nanda Checharia; Wahyu Eko Pujianto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research examines the role of leadership in managing organizational change. The role of leadership in today's organizations, organizational change has become a major and important thing. The role of an effective leader aims to successfully manage change. The aim of this research is to determine the role of leadership in the organizational change process, as an influence on future progress. Literature review and theoretical analysis are combined with qualitative research methodology in this work. Based on the research results, examine the meaning of leadership, the role of leadership for the organization and the leader's efforts to change the organization. Members inspire and motivate change when they participate in decision making and accept change under leadership. Planning, directing and implementing necessary changes becomes easier with collective decisions and those of a single leader. Department members who want to better manage organizational change will greatly benefit from this research.